Association between body weight and distal gut microbes in Hainan black goats at weaning age - Li, Lianbin; Li, Kunpeng; Bian, Zhengyu; Chen, Zeshi; Li, Boling; Cui, Ke; Wang, Fengyang (Frontiers in Microbiology, 2022)
Gut microbiota plays a critical role in the healthy growth and development of young animals. However, there are few studies on the gut microbiota of young Hainan black goats. In this study, 12 three-month-old weaned lambs with the same birth date were selected and divided into the high body weight group (HW) and low body weight group (LW). The microbial diversity, composition, and predicted function in the feces of HW and LW groups were analyzed by collecting fecal samples and sequencing the 16S rRNA V3-V4 region. The results indicated that the HW group exhibited higher community diversity compared with the LW group, based on the Shannon index. The core phyla of the HW and LW groups were both Firmicutes and Bacteroidetes. Parabacteroides, UCG-005, and Bacteroides are the core genera of the HW group, and Bacteroides, Escherichia-Shigella, and Akkermansia are the core genera of the LW group. In addition, genera such as Ruminococcus and Anaerotruncus, which were positively correlated with body weight, were enriched in the HW group; those genera, such as Akkermansia and Christensenellaceae, which were negatively correlated with body weight, were enriched in the LW group. Differential analysis of the KEGG pathway showed that Amino Acid Metabolism, Energy Metabolism, Carbohydrate Metabolism, and Nucleotide Metabolism were enriched in the HW group, while Cellular Processes and Signaling, Lipid Metabolism, and Glycan Biosynthesis and Metabolism were enriched in the LW group. The results of this study revealed the gut microbial characteristics of Hainan black goats with different body weights at weaning age and identified the dominant flora that contributed to their growth.